2023
DOI: 10.1097/ccm.0000000000005849
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Development of Renal Replacement Therapy Indications by Combining the Furosemide Stress Test and Chemokine (C-C Motif) Ligand 14 in a Cohort of Postsurgical Patients

Abstract: OBJECTIVES: Optimal timing of renal replacement therapy (RRT) initiation in severe acute kidney injury (AKI) remains controversial. Initiation of treatment early in the course of AKI may lead to some patients undergoing unnecessary RRT, whereas delayed treatment is associated with increased mortality. This study aims to investigate whether the combination of the furosemide stress test (FST) and AKI-associated biomarkers can predict the development of indications for RRT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…After removing duplicates, 19 articles were evaluated by their titles and abstracts. Out of these, six studies met the criteria for a full-text review [ 18 20 , 24 26 ]. During the literature search process, we found that the RUBY study, authored by Hoste et al [ 17 ], and the subsequent secondary analysis article by Koyner et al [ 24 ] shared the same study population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates, 19 articles were evaluated by their titles and abstracts. Out of these, six studies met the criteria for a full-text review [ 18 20 , 24 26 ]. During the literature search process, we found that the RUBY study, authored by Hoste et al [ 17 ], and the subsequent secondary analysis article by Koyner et al [ 24 ] shared the same study population.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid data duplication, we opted to include the more recent study data from Koyner et al, which also provided the target outcome, for our integrated analysis. From the studies conducted by Jiang et al and Meersch et al, in order to reduce the research heterogeneity, we extracted data from subpopulations within those two studies [ 18 , 20 ]. These studies included information on 952 patients, who had data on the incidence of persistent AKI with urinary CCL14 values, and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If urine output exceeded 200 ml within the consecutive two hours, patients were considered FST positive. The authors demonstrated that a combination of a negative FST test with elevated urinary CCL14 was significantly better in predicting the development of an absolute indication for RRT than FST or CCL14 alone [69 ▪ ].…”
Section: Beyond the Silver Bullet – Combining Biomarkers And Personal...mentioning
confidence: 99%